IMPROVING VOCABULARY MASTERY OF FIRST GRADERS OF TUNAS HARUM BANGSA ELEMENTARY SCHOOL USING VISUAL IMAGE IN READING COMPREHENSION - Yolanda Lionny Victoria; Agnes Widyaningrum (Universitas Stikubank (UNISBANK) Semarang, 2023)
The descriptive qualitative methodology is used in this study. Using the information gathered from test and post-test procedures, this strategy enables researchers to provide detailed explanations. The goal of the test is to demonstrate how students' vocabulary grows as a result of reading passages from their text books. This has a connection to the ZPD theory, according to which kids